2020
DOI: 10.1021/acs.bioconjchem.0c00486
|View full text |Cite
|
Sign up to set email alerts
|

Designed Streptococcus pyogenes Sortase A Accepts Branched Amines as Nucleophiles in Sortagging

Abstract: Sortase-mediated ligation (sortagging) is commonly performed using the Staphylococcus aureus sortase A (SaSrtA) that strictly recognizes the N-terminal glycine residue. In this work, a rational design of Streptococcus pyogenes sortase A (SpSrtA) for improved transpeptidase activity toward different N-terminal amino acid residues was conducted. The generated variant SpSrtA M3 (E189H/V206I/E215A) showed up to 6.6-fold (vs SpSrtA wild-type) enhanced catalytic efficiency. Additionally, M3 retains the specificity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
(57 reference statements)
3
20
0
Order By: Relevance
“…Overall, our data are consistent with recent work where a triple mutant of S. pyogenes SrtA (E189H/V206I/E215A, where E215A is a mutation at the β7–β8 −1 position) resulted in 6.6-fold enhanced catalytic efficiency ( 32 ). In addition, K196T in the catalytically enhanced pentamutant saSrtA protein is also located at the β7–β8 −1 position ( 8 ).…”
Section: Resultssupporting
confidence: 92%
“…Overall, our data are consistent with recent work where a triple mutant of S. pyogenes SrtA (E189H/V206I/E215A, where E215A is a mutation at the β7–β8 −1 position) resulted in 6.6-fold enhanced catalytic efficiency ( 32 ). In addition, K196T in the catalytically enhanced pentamutant saSrtA protein is also located at the β7–β8 −1 position ( 8 ).…”
Section: Resultssupporting
confidence: 92%
“…6E, Table S1 ). This is consistent with recent work where a triple mutant of S. pyogenes SrtA (E189H/V206I/E215A, where E215A is a mutation at the equivalent β7-β8 −1 position) resulted in a 6.6-fold enhanced catalytic efficiency (26). Notably, K196T in the catalytically enhanced pentamutant saSrtA protein is also located at the β7-β8 −1 position (8).…”
Section: Resultssupporting
confidence: 92%
“…Although target sequence recognition by S. aureus SrtA is rigidly selective for a P1’ glycine, this is not true of all Class A sortases, such as those from Streptococcus pneumoniae and Streptococcus pyogenes (10, 30, 34, 35). Building from our previous work, in which spSrtA was found to accept peptides containing Gly-, Ala-, Ser- and other residues at P1’, we have shown here that this broadened substrate scope can be attributed to the sequence of the β7-β8 loop (26). Moreover, variations in β7-β8 loop sequences can substantially impact overall enzyme activity, affording chimeric sortases that outperform their wild-type counterpart i n vitro .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Zou et al 66 have recently reported the design of SpSrtA variants with improved transpeptidase activity towards different N-terminal amino acid residues. Based on sequence alignment of sortase A from different species they identified conserved residues near the active site suitable for mutation.…”
Section: Enzyme Engineering To Broaden Substrate Scopementioning
confidence: 99%